Digital transformation trends in music teaching and training systems - Asztalos Bence (A Juhász Gyula Pedagógusképző Kar Ének-Zene Tanszékének kiadványai, 2022)
The pandemic has greatly accelerated the need for modernisation and digital transformation of education and training systems. NERa2 (A New Era of Digital Platforms in Music Education) Erasmus+ Strategic Partnership emphasises digital creativity in teaching and focuses to actively contribute and support the process of recovery. The partnership promotes intercultural dialogue approaches linking digitalised music education and training. Higher education institutes from various parts of Europe bring their digital music pedagogical expertise to provide a universal and comprehensive tool for the international academic environment based on real practice and experience. The study examines NERa’s implementation of digital components and viewpoints into the traditional music teaching and training systems.